2019
DOI: 10.1073/pnas.1904091116
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of leukemic blasts is not completely blocked in acute myeloid leukemia

Abstract: Hematopoiesis, the formation of blood cells, involves the hierarchical differentiation of immature blast cells into mature, functional cell types and lineages of the immune system. Hematopoietic stem cells precisely regulate self-renewal versus differentiation to balance the production of blood cells and maintenance of the stem cell pool. The canonical view of acute myeloid leukemia (AML) is that it results from a combination of molecular events in a hematopoietic stem cell that block differentiation and drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…For example, recent studies indicated that within certain immunophenotypic fractions such as CD34 + /CD38 -, other factors such as reactive oxygen species content are able to identify which cells are functional LSCs (18,19). Furthermore, mathematical modelling studies of leukaemogenesis have indicated that mature myeloid cells can often have the same genotype as leukaemic blasts, highlighting that differentiation of leukaemic blasts is not completely blocked in the disease (20). A comprehensive single-cell sequencing study by Bernstein et al has indicated intra-tumoural heterogeneity of malignant AML cells and uncovered that some undefined phenotypic markers may be expressed by both malignant and normal cells (21).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies indicated that within certain immunophenotypic fractions such as CD34 + /CD38 -, other factors such as reactive oxygen species content are able to identify which cells are functional LSCs (18,19). Furthermore, mathematical modelling studies of leukaemogenesis have indicated that mature myeloid cells can often have the same genotype as leukaemic blasts, highlighting that differentiation of leukaemic blasts is not completely blocked in the disease (20). A comprehensive single-cell sequencing study by Bernstein et al has indicated intra-tumoural heterogeneity of malignant AML cells and uncovered that some undefined phenotypic markers may be expressed by both malignant and normal cells (21).…”
Section: Introductionmentioning
confidence: 99%
“…It arises due to genetic changes in the DNA of myeloid precursors. It is characterized by an obstruction in differentiation and a continuous division of immature myeloid cells, more precisely leukemic blasts, which impair normal hematopoiesis (20). AML primarily forms in the bone marrow, but in most cases, blasts are also found within the peripheral blood.…”
Section: Acute Myeloid Leukemia (Aml)mentioning
confidence: 99%
“…For providing important information about the general patient’s health, the complete blood count (CBC) is one of the most ordered tests by physicians around the world. Besides being used as a screening, it is essential for the diagnosis and evolutionary control of infectious diseases, medical emergencies, surgeries, traumatology, in addition to chemotherapy and radiotherapy accompaniment 1 and, therefore, considered an essential diagnostic tool by the World Health Organization 2 . The main parameters evaluated in CBC are the total count of red blood cells (RBC), platelets (PLT), and white blood cells (WBC).…”
Section: Introductionmentioning
confidence: 99%